50. Decreased heart rate variability in REM sleep behavior disorder. Issue 4 (April 2016) - Ministeri, C.M.; Modica, A.A.; Coco, D. Lo; Maccora, S.; Maccora, I.
Abstract : The aim of our study was to evaluate the role of decreased heart rate variability (HRV) in patients with REM sleep behavior disorder (RBD) as a marker of autonomic dysfunction. We studied HRV in 9 RBD patients (7 men and 2 women; mean age, 71.3 ± 7.3 years) by means of 5-min segments of single channel electrocardiogram recorded during wakefulness. Subjects with other causes of reduced HRV were excluded. Measures of beat-to-beat RR variability including time domains (mean RR-interval and RR-standard deviation) were assessed. Basal RR interval and RR-DS were within normal range of values in all patients. On the contrary, HRV was decreased after deep breathing and standing-up procedures in all patients. HR-increase to standing up (max HR after 15″from standing-up – mean basal HR) was impaired in 90% of patients. Moreover, after standing-up, RR-DS and RR-ratio were both decreased in 80% of patients. HRV during wakefulness was frequently decreased in RBD patients, suggesting abnormalities of both sympathetic and parasympathetic function. Our findings suggested that decreased HRV measured by routine electrocardiograms may be an early sign of neurodegeneration since RBD patients may later develop synucleopathies, such as Parkinson's disease, and cardiac autonomic dysfunction is also impaired in these neurodegenerative disorders.